Rivaroxaban in Patients with a Recent Acute Coronary Syndrome - Mega, Jessica L; Braunwald, Eugene; Wiviott, Stephen D; Bassand, Jean-Pierre; Bhatt, Deepak L; Bode, Christoph; Burton, Paul; Cohen, Marc; Cook-Bruns, Nancy; Fox, Keith A.A; Goto, Shinya; Murphy, Sabina A; et al. (The New England journal of medicine, 2012)
In patients with acute coronary syndromes, low doses of rivaroxaban were effective in reducing the primary end point of death from cardiovascular causes, myocardial infarction, or stroke. Rivaroxaban also reduced overall mortality, although there was more bleeding. After an acute coronary syndrome, patients remain at risk for recurrent cardiovascular events despite standard medical therapy, including long-term antiplatelet therapy with aspirin and an adenosine diphosphate–receptor inhibitor. This risk may be related in part to excess thrombin generation that persists beyond the acute presentation in such patients. 1 As a result, there has been interest in evaluating the role of oral anticoagulants after an acute coronary syndrome. Improved cardiovascular outcomes were reported for patients who were treated with the anticoagulant warfarin in addition to aspirin. 2 However, widespread use of long-term warfarin in such patients has been limited by challenges associated . . .